Synthesis of Some Novel 2,4-Thiazolidinedione Derivatives and Their Biological Screening as Antidiabetic Agents - Jiwane, S.K.; Singh, V.K.; Namdeo, K.P.; Prajapati, S.K. (Asian Journal of Chemistry, 2010)
Six derivatives of 2,4-thiazolidinedione having dialkyl amine appendage at N-3 position were synthesized and their antidiabetic activity were evaluated. All derivatives were synthesized by the reaction of 2,4-thiazolidinedione with different aldehydes, which further react with different dialkylamine. All derivatives were evaluated for their glucose lowering capability in dexamethasone induced diabetic rat.